Site-specific nutrient management for rice in Nepal: Estimating indigenous nutrient supply, improving fertilizer recommendations, and enhancing yield in the Terai Region - Santosh Marahatta; Shrawan Kumar Sah; Andrew McDonald; Jagadish Timsina; Rupak Karn; Krishna Prasad Devkota (Journal of Agriculture and Food Research, 2025)
To address declining soil fertility and stagnating rice yields in farmers' fields, this study evaluated 4-R (right-source, right-rate, right-time, right-place) principles based site-specific nutrient management (SSNM) strategies and varying potassium application rates in the western foothills of Nepal. Field experiments conducted between 2011–2013 and2022–2023 quantified the indigenous nutrient supply (INS) and evaluated the performance of SSNM strategies. These strategies incorporated real-time nitrogen management using leaf color charts (LCC), soil plant analysis development (SPAD), and Nutrient Expert (decision support tool) along with varying K rates on K-deficient soils to evaluate impacts on yield, nutrient uptake, and nutrient-use efficiencies. The results revealed significant spatial variability in soil nutrient levels, with nitrogen (N) being most limiting, followed by phosphorus (P) and K, with mean INS of 53, 29, and 84 kg N, P2O5, and K2O ha-1. SSNM increased rice yield by 36 % (1.68 t ha−1) over traditional farmer practices and by 12 % over blanket recommendations, while reducing N and P2O5 inputs by 4 % and 28 %, respectively. Potassium application needed to be increased by 80 % to prevent soil depletion, indicating that the current K2O recommendationshould be doubled to 80 kg ha−1 to sustain yield and nutrient uptake. LCC-based N increased yield by 4 % without additional N, while SPAD-based N application further saved 8 kg N ha−1. Farmers' current practices yielded 4.69 t ha−1 reflecting a 33 % yield gap compared to attainable yield (7.0 t ha−1). The combine use of LCC-based N with SSNM and Nutrient Expert achieved yields of 6.61 t ha−1, reduced yield gap just to 5.5 %. Overall, SSNM proved to be a robust strategy for addressing nutrient deficiencies, and improving fertilizer recommendation and use effeciencies in rice, delivering agronomic, economic, and environmental benefits to smallholder systems. However, its wider adoption requires targeted farmers’ training and strengthened extension support.